KEANEKARAGAMAN JENIS SEMUT (Formicidae) DI HUTAN KOTA KABUPATEN KETAPANG KALIMANTAN BARAT - Mustika, Adi; Prayogo, Harri; Anwari, M Sofwan (JURNAL HUTAN LESTARI, 2019)
The diversity of ant species is one of the links in ecosystem stability as decomposing insects as well as food sources so that its existence becomes very ecologically important. Information about the types of ants found in the urban forest of Ketapang Regency is not yet available, therefore the problem of this research is how the diversity of ant species (Formicidae) in the urban forest of Ketapang Regency. This study aims to document the richness and diversity of ant species in the urban forest of Ketapang Regency, West Kalimantan. The method used was purposive sampling and systematic where the placement of traps was carried out according to the presence of ants in terrestrial and arboreal types in secondary forest habitats. Based on the results of research in the urban forest of Ketapang Regency, which was carried out in two types, namely terrestrial type and arboreal type, 10 species of 5 sub-families were found. Sub-families and types of ants found include: Dolichoderinae (Dolichoderus burmanicus, Dolichoderus taprobanae ceramensis), Formicinae (Aphomomyrmex afer, Polirachis browni, Prenolepis fisheri, Chepalotes femoral), Myrmicinae (Crematogester yameni, Crematogester indet), Ponerinae (Odontomachus haematodus), Pseudomyrmecinae (Tetraponera attenuata). The species diversity index (H') in terrestrial type secondary forest habitat (H'= 0.62) and arboreal type (H'= 0.81), the results of the two types in the secondary forest can be concluded that it is still relatively low.Keywords: Ants, Secondary forest habitat, Species diversity